Choline Kinase α Inhibitors MN58b and RSM932A Enhances the Antitumor Response to Cisplatin in Lung Tumor Cells - Juan Carlos Lacal; Rosario Perona; Javier de Castro; Arancha Cebrián (MDPI AG, 2022)
Lung cancer is one of the main causes of death in developed countries, and non-small cell lung cancer (NSCLC) is the most frequent type (80% of patients). In advanced NSCLC, platinum-based chemotherapy is the frontline palliative treatment, but less than 5% of patients achieve prolonged survival. Immunotherapy has recently been proposed as the standard of care (SoC) as either monotherapy or in combination with chemotherapy for advanced NSCLC. The levels of expression of PD-L1 are the only predictive biomarkers for patient assessment. Although around 30% of patients receiving immunotherapy achieve 5-year survival, a significant number does not benefit from this novel therapeutic approach. Therefore, there is a need for novel strategies to improve clinical outcomes. The expression level of choline kinase α (ChoKα) is increased in a large number of human tumors, including NSCLC tumors, and constitutes an independent prognostic factor for early-stage NSCLC patients. Thus, ChoKα has been postulated as a new target drug in cancer therapy. The combination of cisplatin with novel targeted drugs such as choline kinase inhibitors may improve both the survival rates and the quality of life of NSCLC patients and may serve as the basis for the development of new therapeutic approaches. To that aim, we developed several in vitro and in vivo approaches to assess the antitumor activity of a novel combination regimen using cisplatin and ChoKα inhibitors. Our results suggest that a proper combination of specific inhibitors of the NSCLC prognostic factor ChoKα and platinum-based conventional chemotherapy might constitute a new, efficient treatment approach for NSCLC patients. This novel approach may help reduce the toxicity profile associated with cisplatin since, despite the advances in NSCLC management in recent years, the overall 5-year survival rate is still poor.